Deficit in acoustic signal‐in‐noise detection in glycine receptor α3 subunit knockout mice. (18th January 2017) - Tziridis, Konstantin; Buerbank, Stefanie; Eulenburg, Volker; Dlugaiczyk, Julia; Schulze, Holger
Abstract: Hearing is an essential sense for communication in animals and humans. Normal function of the cochlea of higher vertebrates relies on a fine‐tuned interplay of afferent and efferent innervation of both inner and outer hair cells. Efferent inhibition is controlled via olivocochlear feedback loops, mediated mainly by acetylcholine, γ‐aminobutyric acid (GABA) and glycine, and is one of the first sites affected by synapto‐ and neuropathy in the development of hearing loss. While the functions of acetylcholine, GABA and other inhibitory transmitters within these feedback loops are at least partially understood, especially the function of glycine still remains elusive. To address this question, we investigated hearing in glycine receptor (GlyR) α3 knockout (KO) and wildtype (WT) mice. We found no differences in pure tone hearing thresholds at 11.3 and 16 kHz between the two groups as assessed by auditory brainstem response (ABR) measurements. Detailed analysis of the ABR waves at 11.3 kHz, however, revealed a latency decrease of wave III and an amplitude increase of wave IV in KO compared to WT animals. GlyRα3 KO animals showed significantly impaired prepulse inhibition of the auditory startle response in a noisy environment, indicating that GlyRα3‐mediated glycinergic inhibition is important for signal‐in‐noise detection. Abstract : We found specific changes in the ABR signals and impairment of PPI of the auditory startle response in GlyRα3 KO mice indicating that efferent GlyRα3‐mediated glycinergic inhibition in the cochlea is important for signal‐in‐noise detection.